Equine adipose-derived stem cells modulate in vitro neutrophil extracellular trap release by polymorphonuclear neutrophils - Salinas-Varas, Constanza; Espinosa, Gabriel; Muñoz-Caro, Tamara; Conejeros, Iván; Gärtner, Ulrich; Fey, Kerstin; Arnhold, Stefan; Taubert, Anja; Hermosilla, Carlos (Frontiers in Veterinary Science, 2025)
Neutrophil extracellular trap (NET) are thin and long web-like structures composed of DNA and antimicrobial proteins released by activated polymorphonuclear neutrophils (PMN) as part of the innate immune response. Adipose-derived stem cells (ADSCs) represent an accessible, abundant and minimal invasive source of mesenchymal stem cells (MSCs), with high regenerative potential, immunomodulatory and anti-inflammatory properties. Although recognized immunomodulatory properties of ADSCs, their interaction with PMN and their role on NET formation remains poorly characterized. The present study aimed to evaluate the in vitro effects of equine ADSCs on NET formation by equine PMN. Equine ADSCs were isolated from two different sources of adipose tissue, subcutaneous and retroperitoneal adipose stores. Equine PMN were isolated from peripheral blood with a discontinuous density gradient and stimulated with phorbol 12-myristate 13-acetate (PMA) to induce NET release as positive control. Scanning electron microscopy (SEM) and immunofluorescence microscopy (IFM) analyses were performed to assess NET release by equine PMN co-cultured with ADSCs. In vitro IFM-NET quantification revealed a significant NET decrease for PMN co-cultured with ADSCs and PMA. Furthermore, extracellular DNA quantification showed that inhibition of equine NET is dependent on the ADSCs to PMN ratio, for PMA and ionomycin stimulated PMN. Moreover, our findings unveil no modulation of reactive oxygen species (ROS) production by equine PMN when co-cultured with ADSCs. In summary, our results provide evidence of ADSCs on equine PMN, particularly in their capacity to attenuate NET formation and release. These results support the potential role of ADSCs on host innate immune response and thereby maintaining immune homeostasis. Further investigation is needed to better understand the specific molecular pathways involved in NETosis via ADSCs.